PENGARUH REKRUTMEN DAN PENEMPATAN KERJA TERHADAP KEPUASAN KERJA PEGAWAI DEVISI SDM DI KEMENTERIAN KEHUTANAN JAKARTA PUSAT - Cindy Fantika Sari; Edy Krisyanto (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to examine the influence of recruitment and job placement on employee job satisfaction at the Ministry of Forestry, Central Jakarta. Human resources are a strategic factor that determines organizational success. Effective recruitment is expected to produce employees with the right competencies, while appropriate job placement can maximize employee potential in supporting the achievement of organizational goals. However, challenges remain, such as the decline in recruitment quality and job mismatches, which affect employee satis-faction levels.This research employs a quantitative approach using a survey method by distributing questionnaires to 56 respondents. The collected data were analyzed using validity and reliability tests, classical assumption tests, simple linear regression, and multiple linear regression with the help of SPSS version 26. The results show that recruitment has a positive and significant effect on job satisfaction, with a significance value of 0.001 < 0.05. Job placement also has a positive and significant effect, with a significance value of 0.000 < 0.05. Simul-taneously, both variables strongly influence job satisfaction, indicated by a cor-relation coefficient (R) of 0.675 and a coefficient of determination (R²) of 0.456. This means that recruitment and job placement explain 45.6% of job satisfaction, while the remaining percentage is influenced by other factors not included in this study.The findings highlight the importance of implementing transparent and pro-fessional recruitment, as well as job placement that matches employees’ back-grounds and competencies. Continuous improvement in both aspects is expected to enhance employee satisfaction, motivation, and performance within the Minis-try of Forestry, Central Jakarta.